The Impact of Curriculum Reform on Changes in Student Performance and Motivation in Madrasah - Sugito; Moch. Bakhtiar; Ikhwan Tamrozi (Institut Attanwir Bojonegoro, 2025)
This study explores the impact of curriculum reform on student performance and motivation in madrasas. The results of the study show that curriculum reform has a significant positive impact on improving students' academic performance. These findings include progress in test scores, assignment quality, and students' practical skills, which are due to the relevance of teaching materials and the application of innovative teaching methods. In addition, curriculum reform also increases students' intrinsic motivation due to more relevant materials and interactive learning methods. This increase in motivation is directly related to the improvement of academic performance. Internal factors such as cognitive abilities and personal motivation, as well as external factors such as family support and teaching quality, influence the results achieved. Implications for education include the need for regular curriculum updates, the implementation of innovative teaching methods, professional training for teachers, and increased family support to maximize the benefits of curriculum reform in madrasah.